Growth Of 2 Ambon Banana Varieties (Musa Paradisiaca L.) Local Dlock On Some Plant Media At The Acclimatization Stage - Ari Pramuja Adittiya, Ari Pramuja Adittiya; Adnan; Rizky Septika Utami; Mardia Apriani; Rini Suryani (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2023)
ABSTRACT :Curup local ambon bananas are a leading commodity in Rejang Lebong district. Therefore it is necessary to maintain its genetic resources so that they do not become extinct. Tissue culture technique is the most modern method of propagation because it can grow uniformly, is free from pests and diseases, and produces quickly. However, maintenance of tissue culture seedlings at the acclimatization stage needs attention. Therefore researchers will examine the treatment of media and local banana varieties Curup on growth. The research was carried out in the plastic house at Pat Petulai University from December 2022 to March 2023. The materials used were yellow and green Ambon banana seeds resulting from tissue culture, a fungicide with an active ingredient of 80% monkozeb. This study aims to determine the best media and varieties that grow best at the acclimatization stage. The design of this study was a completely randomized design (CRD) with two factors, namely the planting medium and the local Ambon banana variety Curup. Each treatment was repeated 3 times with 2 plant samples so that there were 36 experimental units. Observations were made at the end of the study on all observation variables. The data obtained was then analyzed using the Analysis of Variance (ANOVA) with a level of 1% if there is a difference then it will be tested further with the BNT Test (Smallest Significant Difference). The results showed that good planting media treatment was seen in soil + coffee husk media because it could increase the growth of plant height by 41.02 cm, the number of leaves was 6.92 strands, the stem diameter was 12.3 mm. However, the variable leaf width and leaf length showed good growth in soil + rice husk treatment. The longest leaf width is 12.35 cm and the length of the leaf is 13.51 cm. A good variety is ambon kuning because it can increase the leaf width by 11.65cm. The soil + coffee husk planting media is more dominant in influencing several variables because of the high nutrient content in the media. It can be recommended to Ambon kuning farmers to give good results.